(untitled) (Revista Contexto & Saúde, 2026)
Objectives: The mechanisms underlying visual processing impairment in Obsessive-Compulsive Disorder are still insufficiently understood. The present study aimed to conduct an integrative review regarding how visual processing is affected in individuals with Obsessive-Compulsive Disorder, as well as the implications of these alterations for executive functions. Method: The review used the PRISMA normative guidelines, including studies published between 2015 and 2024, indexed in the PubMed, Scopus, Lilacs and PsycINFO databases. The selection and data extraction process was performed independently and blindly by two authors, following predefined eligibility criteria. Results: The final sample included 14 studies, most of which identified significant impairment in antisaccade tasks in individuals with Obsessive-Compulsive Disorder. Conclusions: These studies provide evidence that specific attentional biases are linked to Obsessive-Compulsive Disorder symptomatology and that these alterations may be associated with deficits in inhibitory control, contributing to symptomatology persistence.